A new xanthone and a new benzophenone from the roots of Garcinia hombroniana. (February 2020) - Salleh, Wan Mohd Nuzul Hakimi Wan; On, Shamsul; Ahmad, Farediah; Sirat, Hasnah Mohd; Taher, Muhammad; Sarker, Satyajit Dey; Nahar, Lutfun
Graphical abstract: Highlights: The root extract of Garcinia hombroniana was investigated. A new xanthone (1 ) and a new benzophenone (2 ) were isolated. Four known compounds were also isolated. The structures were determined on the basis of extensive spectroscopic analyses. Abstract: In this study, the roots of Garcinia hombroniana were chemically investigated, in which novel derivatives of xanthone and benzophenone, known as garcihomxanthone (1 ) and garcihombrianone (2 ), respectively, together with garceduxanthone (3 ), cheffouxanthone (4 ), norathyriol (5 ), and 2, 3′, 4, 5′-tetrahydroxy-6-methoxybenzophenone (6 ) were isolated.. The structures of these compounds were elucidated by extensive spectroscopic techniques and evaluated based on references with previous literature data.